Analyses of primary remanence vector data from a large collection of lava flows: towards improved methodology in paleo-geomagnetism - Kristjansson, Leo (Studia Geophysica et Geodaetica)
Research into the properties of past geomagnetic fields (paleo-geomagnetism) has been carried out worldwide for over half a century. This research utilizes rocks which are to a varying degree inadequate for that purpose, and evaluation of the results is therefore not always on firm ground. One resource which can be utilized to constrain several aspects of the interpretation of other paleo-geomagnetic data, consists of stable primary remanence vectors in large homogeneous collections of dated fresh lava flows. We outline how the available remanence data from several thousand lavas in Iceland may be analysed in a semi-quantitative way to test some of current results, methodology and concepts of paleo-geomagnetism. Among topics where such analysis provides new insights, are the geomagnetic polarity time scale, the frequency distribution of virtual geomagnetic poles in latitude and longitude, and the relative intensity of the magnetic field as a function of virtual pole latitude. Comparison of the scatter in remanence intensities and in absolute paleointensity determinations on Icelandic lavas indicates, along with other evidence, that quality criteria for the latter are in need of revising. It is also confirmed here that long-term changes have occurred in the amplitude of the geomagnetic secular variation; they should be taken into account in studies on other properties of the paleo-geomagnetic field. Leo Kristjansson. Obsahuje seznam literatury